PENERAPAN MODEL DISCOVERY LEARNING MUJA UNTUK MENINGKATKAN LITERASI SAINS SISWA DI KELAS 9B SMPN 7 MUARO JAMBI - Purnamawati, Heni; Basuki, Fibrika Rahmat (EduFisika: Jurnal Pendidikan Fisika, 2021)
This study aims to improve students' scientific literacy skills in grade 9B at the 7th State Junior High School Muaro Jambi by learning Discovery Learning Muja. This classroom action research was conducted in two cycles. The research instruments were learning observation sheets, student observation sheets, scientific literacy tests, attitude questionnaires. The indicator of the success of students' scientific literacy was that at least 50% of respondents have achieved scientific literacy in the good category. The application of Muja's Discovery Learning on plant and animal breeding materials in grade 9B at the 7th State Junior High School Muaro Jambi can improve scientific literacy. 53% of students have reached the good category. Muja's Discovery Learning can be applied to the topics/materials that can be related to the local potential of the Muaro Jambi area. The concept discovery process will be more meaningful if it is carried out through investigations/experiments that emphasize student activities that support the development of scientific literacy.